Quantitative expression of the mutated lamin A/C gene in patients with cardiolaminopathy - Narula, Nupoor; Meder, Benjamin (Journal of the American College of Cardiology, 2012)
The authors sought to investigate the gene and protein expression in Lamin A/C (LMNA)-mutated dilated cardiolaminopathy (DCM) patients (DCMLMNAMut) versus LMNA-wild-type DCM (DCMLMNAWT), and normal controls (CTRLLMNAWT).
Available online 10 October 2012
Gesehen am 27.06.2018